استثمار أموال الزكاة في صندوق الزكاة القطري : دراسة مقاصدية تقويمية - سفران، صالح سعيد صالح (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This dissertation aimed to throw light on the experience of Qatar Zakat Fund in investing Zakat funds, and the contribution of Zakat fund investment to the society; a matter which makes Zakat institutions a prominent role player in social insurance and social development as the principle of its legitimacy. The research problem lies in the explanation of diversity in jurisprudential opinions in regard to the matter, and measurement of the benefits of the fund's investment of Zakat funds. Therefore, the researcher addressed the views of both ancient and modern scholars using inductive method to collect the sayings of jurisprudence scholars on the matter and their proofs. An analytical approach was also employed to investigate the subject of dispute in the matter in order to reach a preponderant jurisprudential opinion. Moreover, this same approach was adopted to analyze the reports issued by Zakat fund in four chapters, the first of which is the dissertation's proposal and its overall structure, followed by the second which is the concept of Zakat fund investment and the views of scholars on the matter. The third is all about the experience of Qatar Zakat Fund in investing the zakat fund with the mention of the models it adopts as well as evaluation of its experience. In the fourth chapter, the researcher exerted his effort in exploring the interests accrued to the investment of Zakat fund both in social and economic aspects in order to determine the level at which the fund benefits from the investment process in achieving its objectives towards the beneficiaries of zakat. This part of research was subjected to the Maqasidic study in order to determine whether the investment process serves these intents. This study was concluded with some findings the most important of which are as thus: Investment of Zakat fund is based on the interest leading to the protection of wealth by maintaining its existence. It also contributes to the achievement of other intents some of which are dependent, such as the intent of monitoring the savings which is a means to achieve the two original intents of Zakat, namely poverty alleviation and empowerment of the poor. As for poverty alleviation, the Zakat fund has achieved it through its designed programs for Zakat beneficiaries. And in order to accomplish the intent of empowering the poor, the researcher proposes to the Zakat fund the activation of investment or productive exchange in order to improve their living standard in the way that will enable them to rely on themselves in providing their needs and elevate their status from Zakat receivers to Zakat payers.